The issue of perezhivanie in the learning process: discussions on the Gymnastics coach education - Bento-Soares, Daniela [UNESP]; Schiavon, Laurita Marconi (Taylor & Francis, 2025)
This article has two main aims: first, to discuss the concept of perezhivanie from a cultural-historical perspective and its relation to the learning process and second, to present examples of perezhivanie’s significance for learning opportunities in Gymnastics coach education. Using dialogical reflection based on the critical companionship method, initial, university-based and continuous professional education will be discussed through our position as educators involved in university and national governing body projects. The article discusses the interconnected role of learning, motivation, and affectivity influenced by the constitution of coaches’ subjectivity. Within this process, emotional and social aspects are related to coach education’s pedagogical strategies. Thus, the study proposes discussions between pedagogical and psychological approaches, better informing the planning of institutional programmes for Gymnastics coach education.